Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Karyawan Pada PT Asian Agri Singingi Hilir Kabupaten Kuantan Singingi - Yulita, Rahma; Wahab, Wirdayani; Menhard, Menhard; Irawan, Candra (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
The purpose of this study was to determine and analyze the effect of workload and work stress on employee performance partially and simultaneously at PT Asian Agri Singingi Hilir. The population in this study amounted to 40 people taken from production employees, while the sample in this study amounted to 40 people using the census method. The analysis in this study used multiple linear regression. Based on the results of the study where the tcount> ttable value is 2.320> 2.02619 and the significance level is 0.026 <0.05, which means that workload partially affects the performance of PT Asian Agri Singingi Hilir office staff employees. Workload with tcount> ttable or 4.225> 2.02619 with a significance level of 0.00 <0.05 which means that workload partially affects the performance of employees of the office staff of PT Asian Agri Singingi Hilir. Workload and work stress have a simultaneous influence on employee performance at PT Asian Agri Singingi Hilir with a calculated F value of 33.931> F-tab of 3.25 with sig. (0,000) < 0.05. Adjusted R Square of 0.628 or 62.8%, this means that 62.8% of the employee performance variable can be explained or influenced by workload and work stress variables. While the remaining 37.2% is influenced by other variables not examined.